Peningkatan Hasil Belajar IPAS Siswa Kelas V Melalui Model TGT dengan Media Peta Sebarhayati - Wiraningrum, Febri; Mursidik, Elly's Mersina; Zahro, Fakhriyatu (JKPD (Jurnal Kajian Pendidikan Dasar), 2025)
This study aims to improve the learning outcomes of Natural and Social Sciences (IPAS) among fifth-grade students at SDN 01 Nambangan Kidul, Madiun City, through the implementation of the Team Games Tournament (TGT) learning model assisted by the SebarHayati Map media. The background of this research is the low student performance on the topic of biodiversity characteristics in Indonesia, particularly in understanding the distribution of flora and fauna. This issue is attributed to the use of conventional teaching methods and a lack of interactive learning media. This is a Classroom Action Research (CAR) conducted in two cycles using a mixed-methods approach. Data were collected through student activity observations and learning outcome tests. The results indicate an increase in the implementation level of the TGT model from 74% in the first cycle to 84% in the second cycle. Furthermore, students' learning outcomes improved significantly: the percentage of students with underperforming scores decreased from 46.67% to 13.33%, while the number of students in the "very good" and "good" categories increased. The use of the SebarHayati Map proved effective in helping students visualize the material contextually and supported the game elements of the TGT model. In conclusion, implementing the Team Games Tournament (TGT) learning model assisted by the SebarHayati Map effectively enhances student learning outcomes and engagement in IPAS learning.